Mobilization Of Human Resources To Increaseprosperity; The European Proceedings of Social & Behavioural Sciences (EpSBS); Vol. 38 : Lifelong Wellbeing in the World (WELLSO 2017) - Potyagaylov (Potyagailov) S. V. Sergey Vitalyevich (2018, 2018)
Title screen